SUSTAINABLE COTTON FARMING PRACTICES: A COMPARATIVE ANALYSIS OF INPUT UTILIZATION - Muhammad Saleem; Ahsan Ali; Shoaib Akhtar; Gulfam Hassan; Rana Muhamamd Waqas; Siyam Naeem; Rabia Fareed; Muhamamd Ramzan (Policy Research Journal, 2025)
Sustainable production involves the conscious use of resources to prevent their depletion while preserving them for future generations. The current study, entitled Sustainable Cotton Farming Practices: A Comparative Analysis of Input Utilization, was conducted to examine the practices of cotton farming that is a cash crop in Pakistan that significantly contributes to the national economy and sustains the textile industry. Despite its importance, many farmers in the country still practice traditional agricultural methods. To address this issue, various organizations are working to raise awareness among farmers about sustainable farming practices to minimize the environmental impact of their activities. This study aimed to evaluate whether farmers were adopting sustainable practices, identify the ones being implemented, and highlight areas requiring improvement. Cotton was chosen as the focus crop due to its intensive requirements for pest management and other farming practices. District Muzaffargarh, located in southern Punjab and known as a cotton belt, was purposively selected as the study area. One tehsil of the district was conveniently chosen, and 100 registered cotton growers were randomly selected for data collection. The data were analyzed using statistical software and Microsoft Excel. The findings revealed that farmers largely refrained from using advanced machinery, such as planking and laser leveling, due to high costs and small landholdings. Regarding irrigation, 34% of farmers irrigated their cotton crops up to ten times, while the remaining irrigated more than ten times. Additionally, about one-third (31%) of farmers did not apply farmyard manure to their fields. Although farmers were aware of biological, physical, and cultural pest control methods, they predominantly relied on insecticides and pesticides for pest management. The study emphasizes the need to educate farmers on adopting environmentally friendly and resource-efficient farming techniques. It is crucial to avoid using banned pesticides that are hazardous to humans, organisms, and the environment. Promoting the conscious use of resources will not only reduce farming expenses but also enhance farmers' profitability. By addressing these challenges, sustainable cotton farming can become a reality, benefiting both the environment and the agricultural economy.